an explanation
most of the reasoning and logic used in mathematical studies is known as deductive reasoning. for example, if fact A is given, then fact B follows.
a different kind of reasoning is known as inductive reasoning. the result is always given and it is necessary to prove that it is true. the method of proof by induction is applied to examples involve the set of natural numbers
n = {1; 2; 3; 4; ... }
a typical example might be:
show that the sum of the first n odd numbers is equal to n^2 (n a natural number)
we could test the formula be choosing the values of n at random, for example:
let n = 3, then 1 + 3 + 5 = 9 and n^2 = 3^2 = 9
so the formula is true for n = 3
similarly, we could repeat the test for several other natural numbers and show that the formula holds for each case. this, however, is not a proof -- but only establishes that the formula holds for the particular values of n which were chosen.
to prove the formula by mathematical induction, we proceed as follows:
* step 1: show that the formula is true for n = 1
* step 2: assume that the formula is true when n = k, where k is any natural number
* step 3: prove that if the formula is true for n = k, it is also true for n = k + 1
* step 4: deduce that the formula is true for any natural number (since it is true for n = 1, it is true for n = 1 + 1 = 2, and then being true for n = 2, it is true for n = 2 + 1 = 3, and so on).
n.b. the statement n = k in step 2 is often called S(k).
the statement n = k + 1 in step 3 is often called S(k) + 1
just an example to help you understand it:
* example: prove by induction that the sum of the first n odd numbers is equal to n^2, that is: 1 + 3 + 5 + 7 + 9 + ... + (2n-1) = n^2
* solution:
* step 1: test to see if statement is correct for n = 1
(2x(1) - 1) = 1^2
1 = 1^2
lhs = rhs
therefore true for n = 1
* step 2: assume the statement is true for k terms, that is, n = k.
s(k) = 1 + 3 + 5 + 7 + ... + (2k-1) = k^2
* step 3: prove the statement is true for (k+1) terms, that is, n = k + 1.
s(k+1) = [1 + 3 + 5 + 7 + ... + (2k-1)] + (2k+1)
that is ... S(k+1) = s(k) + t(k+1)
where s(k) = 1 + 3 + 5 + 7 + ... + (2k-1) = k^2 (from assumption in step 2)
and t(k+1) = (2k+1), substituting k = k+1 (adding another term for s(k + 1).
= k^2 + (2k+1)
(the RHS of our assumption in step 2) + the added term k+1
= (k+1)^2
if the statement is true for n = k, then it is also true for n = k+1 because the sum of the first (k+1) terms is equal to the perfect square (k+1)^2.
* step 4. since the statement is true for n = 1, then BY INDUCTION it must also be true for n = 1 + 1 = 2. it follows that it must also be true for n = 2 + 1, and so on. hence it must be true for all natural numbers n.